FACTORS INFLUENCING THE DEMAND FOR AGLAONEMA ORNAMENTAL PLANTS IN PEKALONGAN DISTRICT, EAST LAMPUNG REGENCY - aditia dwi saputra (Universitas Galuh, 2025)
Aglaonema plants are known for the beauty of their leaf colors and shapes, and have a growing market both offline and online. This study aims to analyze the factors that influence the demand for aglaonema ornamental plants in Pekalongan District, East Lampung Regency, and to calculate the average income of the plant sellers. This study uses a survey method with a quantitative approach and multiple linear regression analysis techniques. The number of respondents was 45 consumers who were selected incidentally. The results of the study showed that the variables of aglaonema price, the price of other ornamental plants, consumer income, and taste had a significant effect on the demand for aglaonema. The results of the analysis also showed that the average income of aglaonema ornamental plant sellers was IDR 30,057,690 per month.Keywords: aglaonema, price, income, demand, preference